Transforming Linear Laser Cutting machine Into Laser Lathing – An Empirical Investigation & Evaluation of Roundness Quality - Sivarao, Subramonian; Nur Izan Syahriah, Hussein; Raja Izamshah , Raja Abdullah; Mohd Amran, Md Ali; Mohd , Hadzley (2012)
Lasers are widely used in industries as cutting tools due to ultra-flexibility cutting capabilities in obtaining high quality end product while posing advantage of quick set up, non-mechanical contact mechanics, and small region of heat affected zone. This paper presents the laser lathing performance of 2D CO2 flatbed laser cutting machine by investigating the roundness quality. A specially designed mechanism was developed to clamp and spin a steel rod of 10mm diameter cylindrical workpiece on X to Y sacrificial table. Three significant cutting parameters were controlled in this experiment namely; cutting speed, spinning speed and depth of cut. The experiments were carried out based on DOE full factorial matrix design. The results were realistic, promising and efficient as compared to manual lathes within the same range of workpiece properties and dimension.